2007
DOI: 10.1089/scd.2007.0034
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Enhances Extracellular Matrix-Induced Gene Focusing and Promotes Osteogenic Differentiation of Human Mesenchymal Stem Cells Through an Extracellular-Related Kinase-Dependent Pathway

Abstract: Human mesenchymal stem cells (hMSCs) are a population of multipotent bone marrow cells capable of differentiating along multiple lineages, including bone. Our recently published proteomics studies suggest that focusing of gene expression is the basis of hMSC osteogenic transdifferentiation, and that extracellular matrix proteins play an important role in controlling this focusing. Here, we show that application of a 3-5% tensile strain to a collagen I substrate stimulates osteogenesis in the attached hMSCs thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…Furthermore, at each time point tested (days 2, 4, and 5), the strained population always lies closer to the osteoblasts than the unstrained population. This is consistent with our previous finding that application of tensile strain accelerates the osteogenic differentiation of hMSC [31]. …”
Section: Resultssupporting
confidence: 94%
“…Furthermore, at each time point tested (days 2, 4, and 5), the strained population always lies closer to the osteoblasts than the unstrained population. This is consistent with our previous finding that application of tensile strain accelerates the osteogenic differentiation of hMSC [31]. …”
Section: Resultssupporting
confidence: 94%
“…Early studies with MSCs showed that uniaxial strain will induce transient increases in collagen I expression and alignment along that axis [58]. Further, a 3-5% tensile strain on a collagen I substrate can induce osteogenesis in MSCs [59], and biaxial stretching systems can influence alignment of MSCs via mechanosensing [60]. Following from this, the imposition of cyclical tensile strain to mimic the loading and unloading of the skeletal system was shown to promote osteogenesis and angiogenesis on three-dimensional collagen I scaffolds [61].…”
Section: The Physical Worldmentioning
confidence: 99%
“…7,23,39 These cells have been shown to readily differentiate down an osteogenic pathway in response to both chemical 8,33,42 and mechanical 30,49,54,66 stimulation. However, in order to produce a tissue engineered bone construct with similar mechanical properties to native tissue, the proper combination of mechanical and chemical stimuli for functional bone tissue engineering needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, although MSCs readily undergo osteogenic differentiation. 21,30,37,49,66 isolating bone marrow is a non-trivial procedure for patients and the number of cells recovered is limited. 6,37,41 Adipose-derived adult stem cells (ASCs) are abundant and more easily obtained.…”
Section: Introductionmentioning
confidence: 99%